(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: The notion of normalcy is often treated as natural and universal; however, it is a socially and culturally constructed concept shaped by power, discourse, and institutional practices. Societal definitions of “normal” function as standards through which differences in body, intellect, race, class, and gender are evaluated and frequently stigmatized. This links the politics of normalcy closely with the politics of culture. Purpose: This paper aims to critically examine how normalcy is constructed and how it operates within cultural systems to produce hierarchy and exclusion. It focuses on disability as a central example while extending the analysis to broader cultural processes involving identity, power, and social classification. Design/Methodology/Approach: The study adopts a qualitative, interpretive, and theory-driven methodology based on textual and conceptual analysis. It engages with key contributions from disability studies, cultural studies, and Marxist and poststructuralist theory to analyze how norms and meanings are historically produced and maintained. Findings: The study finds that categories of “normal” and “abnormal” are historically contingent rather than fixed. Disability is shown to be socially constructed through cultural values and institutional practices, not merely biological conditions. Additionally, culture is revealed as a non-neutral domain where meanings are produced, contested, and institutionalized, reinforcing hierarchies related to class, race, gender, and identity. Conclusion: The paper concludes that the politics of normalcy and culture are deeply intertwined, operating through processes of classification, exclusion, and hierarchy. However, these structures are not immutable and can be challenged through critical theory and inclusive cultural practices. Recognizing the constructed nature of normalcy enables the development of a more democratic and inclusive understanding of human diversity. Keywords: Normalcy, disability, culture, stigma, identity